Impact of rainy and dry seasons on eucalypt fuelwood quality logs stored in piles : a case study in Brazil - Eufrade-Junior, Humberto de Jesus (Array, 2021)
The natural drying of fuelwood is a common practice to improve its quality and increase the efficiency in the biomass-based energy supply chain. The objective of this work was to analyze the effect of seasons on the physical and chemical properties of wood logs stored in piles for energy purposes. The logs of Eucalyptus urophylla were stored in two periods of 160 days each throughout the year, autumn–winter (dry season) and spring–summer (rainy season). During the 320 days, the moisture content of wood and the weather parameters were measured daily. After the natural drying, the moisture content (wet basis) of wood reached 29.6%, and there was an increase of 47.6% in the low heating value (12.4 MJ kg-1 wet basis) after the storage in the autumn–winter, which is the most suitable period for air–drying of logs. The rainy storage reduced the higher heating value of wood, which suggested a biological degradation of biomass.